UMP, MBK seal collaboration in innovation development and environmental sustainability - Mimi Rabita, Abdul Wahit (2023)
KUANTAN, 5 July 2023 - Universiti Malaysia Pahang (UMP) has entered into collaboration with Kuantan City Council (MBK) to improve services and boost the productivity of Kuantan city development and commercialisation of product innovation that can benefit both parties.